Wind Uplift Performance Evaluation of Adhesive Applied Roofing Systems - Murty, Bona (University of Ottawa (Canada), 2010)
Understanding how a roof performs under wind action is crucial to improve the roof design. The present study contributes to an ongoing collaborative research and development project, "Evaluation of wind uplift resistance of Adhesive Applied Roofing Systems (AARS)". The objectives of the project are to develop wind uplift resistance standards and design guidelines for AARS. The project has the following tasks: (1) Task 1: Pullout Testing; (2) Task 2: Peel Testing; (3) Task 3: Wind Uplift Testing; (4) Task 4: Numerical Modeling; (5) Task 5: Development of Design Guidelines. With respect to Task 1 and Task 2, Current (2009) and Wu (2008), respectively, developed new testing procedures. These testing procedures apply static tensile and shear loading to simulate wind uplift and peel forces on the AARS specimens. A dynamic testing procedure that accounts for the wind-induced pressure fluctuations is required for the comprehensive evaluation of the AARS wind uplift performance. The present dissertation contributes to the objective of the AARS project via Task 3 and Task 4. Accomplishments of this dissertation are grouped into two parts. Part 1 develops a laboratory dynamic-testing procedure for AARS wind uplift resistance evaluation and Part 2 presents a three dimensional finite element (3D FE) model to analyze AARS performance. Part 1: Currently, there is no dynamic testing procedure available to evaluate wind uplift performance of rigid roofing systems such as AARS. Towards the development of a dynamic testing procedure, the present study documented the performance of rigid systems under wind effects. Differences in roof system responses were studied by comparing the wind tunnel data of flexible roofs with that of rigid roofs. Analysis of the pressure time histories data using probability distribution function and the power spectral density verified that these two roof types exhibited different system responses under wind forces. Wind-induced pressure fluctuations were found to be higher for flexible roofs in comparison to rigid roofs. A new load cycle for the evaluation of rigid roofing system was developed by applying a rain flow counting method. The newly developed load cycle was validated with the experimental investigation. Thirty full scale mock-ups of AARS were constructed and tested for the experimental investigations. The experimental investigations provided key information on the wind uplift performances of AARS under static and dynamic loading, the effects of number of cycles, the variability of the components, the weakest links, the adhesive curing time, and the failure modes. It was concluded that the newly developed load cycle was more appropriate for the wind uplift performance evaluation of rigid roofing systems such as the AARS. It also was shown that the newly developed load cycle provided a similar wind uplift rating and had shorter testing time in comparison to the existing CSA 123.21-04 load cycle. This new knowledge will be incorporated into the future edition of the CSA 123.21-04 standard. Part 2: A 3DFE model was developed and benchmarked with experimental investigation. The FE analysis showed that the use of different adhesive application techniques significantly influenced the uplift resistance capacity of AARS. The uplift resistance capacity in terms of stress can be estimated when different adhesive application methods are used. The FE analysis also demonstrated the effect of adhesive thicknesses and type of insulation joints on the AARS uplift resistance capacity. The results from the FE model simulations can be used for the development of design guidelines for AARS.
Keywords: Engineering, Civil.